1988
DOI: 10.1104/pp.87.2.447
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Metabolism of Lemna minor L.

Abstract: Aminooxyacetate, a known inhibitor of transaminase reactions and glycine decarboxylase, promotes rapid depletion of the free pools of serine and aspartate in nitrate grown Lemna minor L. This compound markedly inhibits the methionine sulfoximine-induced accumulation of free ammonium ions and greatly restricts the methionine sulfoximine-induced depletion of amino acids such as glutamate, alanine, and asparagine. These results suggest that glutamate, alanine, and asparagine are normally catabolized to ammonia by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…In the comparative analyses of '4N-and '5N-grown fronds and the samples from experiments in which AOA was supplied, two internal standards were employed; L-a-amino-nbutyrate (for the neutral + basic amino acid fraction) and La-aminoadipic acid (for the acidic amino acid fraction), with both internal standards (250 nmol each) added to the samples after methanol:chloroform:H20 phase-separation of the methanol extracts. In the MSO experiments described, no internal standards were employed (11 ( 11) confirmed that greater than 95% of the asparagne was hydrolyzed by asparaginase in these treatments within 1 h. After 1 h, samples were applied to 2.5 x 1 cm columns of Dowex 50-H+, washed with 6 mL H20 and amino acids eluted with 6 mL 6 M NH40H, concentrated to dryness, derivatized to N-HFBI amino acid derivatives (2,13), and analyzed by GC (2, 13) to determine the relative proportions of N-HFBI-0-cyanoalanine and N-HFBI-aspartate.…”
Section: Isolation Of Soluble Nitrogen Poolsmentioning
confidence: 93%
See 3 more Smart Citations
“…In the comparative analyses of '4N-and '5N-grown fronds and the samples from experiments in which AOA was supplied, two internal standards were employed; L-a-amino-nbutyrate (for the neutral + basic amino acid fraction) and La-aminoadipic acid (for the acidic amino acid fraction), with both internal standards (250 nmol each) added to the samples after methanol:chloroform:H20 phase-separation of the methanol extracts. In the MSO experiments described, no internal standards were employed (11 ( 11) confirmed that greater than 95% of the asparagne was hydrolyzed by asparaginase in these treatments within 1 h. After 1 h, samples were applied to 2.5 x 1 cm columns of Dowex 50-H+, washed with 6 mL H20 and amino acids eluted with 6 mL 6 M NH40H, concentrated to dryness, derivatized to N-HFBI amino acid derivatives (2,13), and analyzed by GC (2, 13) to determine the relative proportions of N-HFBI-0-cyanoalanine and N-HFBI-aspartate.…”
Section: Isolation Of Soluble Nitrogen Poolsmentioning
confidence: 93%
“…Plant tissue (0.3-0.5 gfw) was harvested and extracted in methanol (10 mL) as described previously (2,11,13), and amino acids separated into neutral + basic and acidic amino acid fractions by Dowex 50-H+ and Dowex 1-acetate ion exchange chromatography as described previously (2,11,13). In the comparative analyses of '4N-and '5N-grown fronds and the samples from experiments in which AOA was supplied, two internal standards were employed; L-a-amino-nbutyrate (for the neutral + basic amino acid fraction) and La-aminoadipic acid (for the acidic amino acid fraction), with both internal standards (250 nmol each) added to the samples after methanol:chloroform:H20 phase-separation of the methanol extracts.…”
Section: Isolation Of Soluble Nitrogen Poolsmentioning
confidence: 99%
See 2 more Smart Citations
“…Attention was therefore focused on blocking three potential biosynthetic points. These points, and the specific inhibitors tested, were (a) blocking transamination with transaminase inhibitors (aminooxyacetic acid (AOAA), 11 (22)(23)(24), and 2-methylglutamate (MeGlu), 12 (25)) or amidotransferase inhibitors (azaserine, 13 (26), and 6-diazo-5-0x0-Lnorleucine (DON), 14 (27)); (b) blocking the availability of La-arginine with a L-a-arginine biosynthetic inhibitors (L-arginine hydroxamate (ArgH), 15 (28,29), and 12); and (c) blocking N-methylation with a methyltransferase inhibitor (L-ethionine (Eth), 16 (30, 3 1)).…”
Section: A R' = R~= Hmentioning
confidence: 99%